Women and politics: a case study of political empowerment of Indian women. Issue 7 (9th April 2020) - Sharma, Eliza
Abstract : Purpose: This paper aims to identify the dimensions of the political empowerment of Indian women and assess the factors responsible for the lacunas that hold women back in their potential. Design/methodology/approach: The research was based on primary data collected through a personal interview method from a sample of 68 women managers working in five different sectors of the Indian economy, namely; IT, education, telecom, banking, and hospitality sector. Further, data on the five factors from a sample of 423 women employees from the above-mentioned sectors have been collected and analyzed using a multiple regression model with control variables (marital status and generation gap). Findings: The major factors churned out that are needed for the political empowerment of women are namely, information or awareness, family support or family environment, legal environment, political environment, and personal ambitions or internal motivation. Originality/value: The present study has presented new insight into the field of women and politics by providing a case study into the dimensions of political empowerment among Indian women. The pilot model developed in this study can be initiated and replicated across the land on being successful.